Effects of social customer relationship management strategy on relationship quality in five-star hotels in Nairobi, Kenya - Muraya, Kaguma Moses; Korir, Jacqueline; Bor, Thomas (International Journal of Economics, Business and Management Studies, 2023)
The study specifically determined the effect of Social CRM strategies dimensions on relationship quality in five-star hotels in Nairobi, Kenya. Malthouse Social CRM house model anchored the study. The study utilized a sequential explanatory research design with a target population of 987,883 customers from online hotel check-ins for 5 years, from three five-star rated hotels in Nairobi purposively selected. A sample size of 400 was selected using simple random sampling techniques used to identify final respondents. Data was collected from customers using a structured questionnaire. Quantitative data were analyzed using the Structural Equation Model (SEM). The results indicated a positive and significant effect of the Social CRM strategies dimension on relationship quality. Social CRM strategies can be an effective way for hotels to improve the quality of relationships with their customers and build a stronger brand reputation. it is recommended that hotels in Nairobi, Kenya continue to utilize social CRM strategies to enhance their relationship quality with customers. This can include prominently displaying favorable reviews on social media pages, inviting customer feedback, engaging with them through contests, surveys, and other activities, and utilizing virtual tours and other interactive experiences to build loyalty and engagement.